The Servant tradition of Isaiah in the Dead Sea scrolls - Betz, Otto 1917-2005 (1995)
Since many copies of the book of Isaiah were found at Qumran, it would appear that this book was highly honoured by the Essenes who lived there. Yet in none of the sectarian writings is there either a quotation from or explicit reference to the Servant Songs in Isaiah. A careful examination of the linguistic and conceptual elements of these songs and certain sectarian writings reveals a correlation between the biblical figure and role of the Servant and the sectarian Teacher of Righteousness and priestly Messiah.
Keywords: book of Isaiah; Essenes; Linguistic and conceptual elements; Qumran; Sectarian writings; Servant Songs